Assessing Mosque Accessibility and Evacuation Capacity in a Dense Urban Area: Case Study of Keuramat, Banda Aceh - Shah, Azlan; Ahmad Muhajir; Rauzatul Jannah; Husnus Sawab (Jurnal Serambi Engineering, 2026)
Densely populated urban areas face high disaster risk due to limited open space, constrained evacuation routes, and insufficient emergency shelter capacity. This study evaluates the evacuation performance of two mosques in Keuramat Village, Banda Aceh, with contrasting spatial characteristics, including floor configuration, courtyard availability, and building scale. The study applies three GIS-based analyses: Euclidean buffer analysis, shelter capacity assessment, and household-to-mosque pedestrian network simulation. Results show that 743 residential buildings (96.99%) are located within a 300 m radius of a mosque, and 3,376 people (99.88%) can reach the nearest mosque within 10 minutes on foot. However, under capacity-constrained allocation, the effective accommodation level drops to only 53% of the total population. Baiturrahmah Mosque provides greater evacuation capacity (1,222 people) than Al-Ikhlas Mosque (572 people), mainly due to its larger courtyard area. These findings demonstrate that high accessibility alone does not guarantee adequate evacuation performance when shelter capacity is limited. The study highlights the need to integrate accessibility and capacity in mosque-based evacuation planning and supports the inclusion of mosques as distributed evacuation points in dense urban areas.